Photocatalytic reductive sulfonylation and 1, 2-alkyl migration cascades of vinyl cyclobutanols: A synthesis of β-sulfonated cyclopentanones. Issue 2 (17th January 2020) - Kim, Joo Hee; Kim, Dae Young
Abstract: A photoredox strategy to access β-sulfonated cyclopentanones from the reaction of vinyl cyclobutanols with sulfonyl chlorides is described. This reaction employs the inexpensive and easily accessible sulfonyl chlorides as a sulfonyl radical source. The present synthetic protocol is a convenient way to prepare β-sulfonated cyclopentanones. Graphical Abstract: